L’enseignement privé français au Sénégal et l’effet établissement - Suzie Guth (Cahiers de la Recherche sur l'Education et les Savoirs)
The private French schools in Senegal give way to a specific School trend. The schools enrolment is specific to the high rates of the tuition fees, to the French diplomas and to the social classes of the pupils mostly issued from the middle classes and upper classes. Three schools have been studied: a primary school in Saint Louis, the Lycée Louis Mermoz in Dakar and the state Lycée Lamine Gueye (ex Lycée Van Vollenhoven) in Dakar. All three schools enroll in a different way: the Saint Louis school gives scholarships to support the school, in Dakar, the Lycée Mermoz can’t enroll all the pupils and the state Lycée Lamine Gueye enrolls all the pupils, but many a parent would rather send his children to a nearby private school if only they could afford it; they think the protests and strikes lessen the school attendance.